IMPROVING THE QUALITY OF FISHERMEN'S HUMAN RESOURCES (HR) THROUGH ORGANIZED, COORDINATED HR MANAGEMENT AND UTILIZING TOURISM ON LONTAR BEACH - Titus Indrajaya; Syech Idrus; Suflani Suflani; Nurdin Natan; Khaeruman Khaeruman (Yayasan Education and Social Center, 2021)
This PKM takes the object of devotion, namely fishermen who are residents of Lontar Beach Village. Service partners to PKM is the village manager. The problems taken from the productivity of fishers are still not maximal Not yet skilled fishermen villages management of fish catches well (such as frozen food, food variations etc.), and still lack of human resource management for fishers Lontar Beach village. The PKM programprovided is in the form of seminars on how to improve and improve the quality of fishers of Lontar Beach Village Tirtayasa Subdistrict and training how to store, process and market fishermen's catches at Lontar Beach In the future it is expected that the quality of existing human resources is fishermen of Lontar Beach Village District Tirtayasa can be improved and improved so that it can contribute more to the Village of Lontar Beach Tirtayasa Subdistrict. Lontar Beach fishers have entrepreneurship knowledge that has business ethics, handle customer complaints and how to market good products, and future service is expected to provide more practical training. to provide them with provisions in the face of competition and see opportunity in the future